Potensi Emisi Gas Rumah Kaca dari TPA Galuga dan Kelayakan Finansial Teknologi RDF - Asyifa, Nuraulia; Wijayanti, Pini (Jurnal Sosioteknologi, 2025)
Many cities are confronting significant challenges due to the rising volume of waste. This surge in waste generation not only risks overcapacity but also contributes to increased greenhouse gas (GHG) emissions. This study aims to estimate the amount of waste directed to the Galuga landfill, evaluate the potential GHG emissions resulting from the landfill, and analyze the financial viability of implementing Refuse DerivedFuel (RDF) technology, which has the potential to reduce waste volumes. This research employs three key methods: 1) Multiple Linear Regression (MLR) to identify the factors that influence waste generation, 2) the IPCC guidelines for National Greenhouse Gas Inventories Volume 5 to estimate potential greenhouse gas emissions, and 3) a financial feasibility analysis to evaluate the viability of implementing RDF technology.The results show that the volume of waste directed to the Galuga landfill in 2022 was 195,787.10 tons, with a projected increase of 2.43% by 2030, bringing the total to 200,544.26 tons. The potential greenhouse gas (GHG) emissions from waste generated at the Galuga landfill are estimated to be 109 kt CO2e in 2030, reflecting a decrease of 29.48% compared to 2022. Furthermore, the plan to implement RDF technologyis deemed financially viable, as it fulfills the necessary criteria for Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost (B/C) Ratio, and Payback Period. Therefore, the governments may introduce various incentives to promote the adoption of RDF technology, stricter waste segregation is essential for better RDF quality, and attracting private investment through PPPs can enhance RDF infrastructure.